Design, implementation & analysis of a low-cost, portable, medical measurement system through computer vision - Van der Westhuizen, Gareth (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.